Enhancement in structural and optical properties of copper tin sulphide (CTS) thin films via sulphurization process - Hossain E.S.; Chelvanathan P.; Bais B.; Azmi N.; Shahahmadi S.A.; Yussof Y.; Sopian K.; Amin N. (Elsevier Ltd, 2023)
Copper compounds; IV-VI semiconductors; Layered semiconductors; Optical properties; Thin film solar cells; Thin films; Tin compounds; Cu2SnS3 (copper tin sulphide); Device performance; Polycrystalline copper; Secondary phase; Structural and optical properties; Sulfide thin films; Sulphurization; Sulphurization time; Thin-films; Tin sulfide; Sulfur compounds